Clinical significance of T helper cell subsets in the peripheral blood and bone marrow of patients with multiple myeloma - Zhang, Liangjun; Zhong, Huixiu; Fan, Jiwen; Mao, Jiansen; Li, Yi (Frontiers in Immunology, 2024)
Background: T helper (Th) cell subsets primarily assist B cells in differentiating into plasma cells in the germinal center. The mechanism of malignant transformation of plasma cells is an important target for the clinical treatment of MM; however, the mechanism remains unclear.Methods: We collected the peripheral blood (PB) and bone marrow (BM) samples of 33 patients with MM. In addition, the PB was also collected from 25 normal healthy controls (HCs). We analyzed the percentages of Th cell subsets in the PB and BM samples of patients with MM.Results: Tfh/CD4 + were positively correlated with the proportion of myeloma cells in the BM and PB samples (r = 0.592, P = 0.002 and r = 0.510, P = 0.010 respectively), and showed a strong correlation between the BM and PB samples (r = 0.6559, P = 0.0095). In the PB samples, the percentages of Th2/CD4 + and Tfh2/Tfh cells were significantly lower in patients with MM than in HCs (P = 0.00013 and P = 0.0004, respectively), whereas the percentage of Th17/CD4 + and Tfh17/Tfh was significantly higher in newly diagnosed patients with MM than in HCs (P = 0.0037 and P = 0.03, respectively), and all these cells showed a good predictive value for MM (area under the curve [AUC] 0.781, = 0.792, = 0.837, and 0.723 respectively). In the PB samples, all subsets of PD-1 + ICOS -Tfh showed a noticeable downward trend in MM from newly diagnosed to non-remission and remission groups. In contrast, all subsets of PD-1 -ICOS + Tfh increased gradually. Conclusions: Th cell subsets play an important role in the occurrence and development of MM and may provide a fundamental basis for identifying new immunotherapy targets and prognosis.